Comorbid Depression and Substance Abuse in Domestic Homicide: Missed Opportunities in the Assessment and Management of Mental Illness in Perpetrators - Oliver, Casey L. (Journal of interpersonal violence, 2021)
Almost 40% of murdered women are victims of domestic homicide across the world. However, research has yet to examine comorbid depression and substance abuse in domestic homicide perpetrators, despite comorbid mental health conditions being associated with homicide in the general population. A retrospective case analysis approach was performed using domestic homicide cases that had been reviewed by the Domestic Violence Death Review Committee in Ontario, Canada. Group comparisons were made by compiling cases into groups based on perpetrators with depression and/or substance abuse: a no history of depression and/or substance use group, depression only group, substance abuse only group, and comorbid depression and substance abuse group. Statistical analyses compared groups on number and types of risk factors and service provider contacts. A major finding of the current study was the resounding lack of mental health care and batterer intervention program engagement across groups. Results also indicated that perpetrators with comorbid depression and substance abuse have an elevated number of risk factors for domestic homicide and elevated number of service provider contacts. Furthermore, results indicated that perpetrators with comorbid depression and substance abuse had an increased likelihood of having engaged in hostage-taking behavior and increased likelihood of having contact with mental health and health care providers. The study demonstrates the necessity for future research into the barriers associated with help-seeking by perpetrators, family and friends, as well as the barriers to agency referral and to mental health agencies providing service to perpetrators. It also highlights the need for service providers to take multiple mental health conditions into account when working with perpetrators of domestic homicide. Overall, this study underscores the importance of mental health and domestic violence training for service providers in different sectors. Moreover, it emphasizes the necessity of collaboration among service providers to address both violence-specific and mental health-specific concerns in perpetrators of domestic violence.